The roles of perceived value in the relationship between environmental concerns and revisit intention to Green Resorts in Malaysia - Nor Rabiatul Adawiyah, Nor Azam (2019)
Green resort management has emerged as an increasingly popular academic and practical subject matter within the business field. In the competitive hospitality and tourism industry, revisiting intention of a guest has been highlighted as an essential research topic. Despite the considerable number of researches that have looked into repeating guests, the fundamental motivations and influences that cause guests to repeat their visits are still vague and unclear. Therefore, this study examined the mediating role of perceived value between environmental concern and guests’ intentions to revisit green resorts. The model presented in this study is composed of seven constructs, namely four perceived value components (functional value, social value, epistemic value, and emotional value), two environmental concern components (environmental knowledge and environmental awareness), and revisit intention. The underlying theory of this study is based on the Social Exchange Theory (SET). The adopted theory explores on how guests evaluate their experience of staying in green resorts, with particular attention on visiting, seeing, learning, enjoying, and experiencing different lifestyles, along with the potential of incurring sacrifices. Data was gathered from questionnaires distributed to 450 guests who stayed in three green resorts in Langkawi and Penang. Regression analysis was employed to test the relationship between perceived value, environmental concern, and revisit intention. The analysis’s outcomes have exhibited a positive relationship between environmental concerns and revisit intention. The results indicated that functional and epistemic values were the main sources of influence on revisiting intention. The significant findings of the study are two-fold, first it is proven that environmental awareness strongly influences guest’s intention to revisit, and second, the functional and epistemic values partially mediate the relationship between environmental awareness and revisit intention. Theoretically, this study enriches the literature by offering detailed explanation regarding the influences of environmental concern and perceived value on revisit intention. The research gap is addressed by clarifying the relationship between environmental concern and revisit intention, with perceived value as the mediating variable. Practically, these outcomes benefit the operation of resorts in terms of understanding the importance of developing environmental concern among guests and therefore marketing perceived value to them.